Literacy activities in madrasah education: examining student engagement, curiosity, and appreciation in character formation - Dzakiroh, Aisyah; Damni, Albertos (UIR Press, 2026)
Literacy activities have increasingly been recognized as a strategic approach in strengthening students’ character within educational settings. This study aims to analyze the role of literacy activities in shaping the character of activeness, curiosity, and appreciation of achievement among seventh-grade students at MTsN 1 Kota Sungai Penuh. This research employed a descriptive qualitative approach, using observation, in-depth interviews, and documentation as data collection techniques. Data were analyzed using Miles’ interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that consistently implemented literacy activities enhance students’ activeness, including increased confidence in reading aloud, active participation in discussions, and initiative in accessing reading resources. Students’ curiosity develops through the freedom to choose reading materials, the emergence of critical questioning, and independent exploration of information. In addition, appreciation practices such as praise, recognition of students’ work, and the “most active reader” program foster intrinsic motivation, self-confidence, and a culture of appreciation. The novelty of this study lies in its integrated analysis of literacy activities in developing activeness, curiosity, and appreciation of achievement within a madrasah context. However, this study is limited to a single school setting. The implications suggest that literacy activities can serve as an effective strategy for strengthening students’ character through consistent and contextual implementation.